Residual and technical tax efficiency scores for Brazilian municipalities: a two-stage approach - Sousa, Maria da Conceição Sampaio de; Araújo, Pedro Lucas da Cruz Pereira; Tannuri-Pianto, Maria Eduarda (Estudos Econômicos (São Paulo), 2012)
Recurrent fiscal imbalances in terms of tax and expenditure assignments among central and local governments are a critical issue in public finance. To equalize tax capacities, cope with spillovers or to achieve national policy objectives, central governments often provide transfers to lower levels of government. These transfers may affect the incentives to improve fiscal performance because they may induce low tax effort in the regions (Litvack, Ahmad and Bird, 1998; Boadway et al., 1999).